Intelligent systems-enabled decentralized e-government framework for higher education in Iraq: a conceptual data fusion approach - Fuad, Ali; Mohd Aboobaider, Burhanuddin; Abd Ghani, Mohd Khanapi (2023)
The article presents an intelligent systems